Explicit Teaching of Socio-Affective Language Learning Strategies to Beginner EFL Students - Fandiño Parra, Yamith José (Íkala, Revista de Lenguaje y Cultura, 2010)
The objective of this paper is to explicitly teach socio-affective language learning strategies (SLLS) to positively impact the beliefs, attitudes, anxieties, and motivations of a group of beginner EFL students at the Centro Colombo Americano in Bogota (Colombia). Therefore, an action research study was carried out with 17 students who were taking a Basic English course. They answered two open-ended questionnaires, one at the beginning and the other at the end of the study; they also answered questions using a rating scale about affective factors and participated in a set of socio-affective activities designed and implemented by the researcher. As a result of the study, an explicit strategy instruction in SLLS is helpful in heightening learner awareness of the importance of paying attention to their own feelings and social relationships as part of their learning process. Thus affective factors are important considerations that both teachers and students need to reflect on to gain a deeper understanding of the nature of language learning and, ultimately, to gain insight about themselves. Received: 10-08-09 / Accepted: 04-12-09 How to reference this article: Fandino Parra, Y. J. (2010). Explicit Teaching of Socio-Affective Language Learning Strategies to Beginner EFL Students. Íkala. 15(1), pp.145-169